2008
DOI: 10.1016/j.neuroimage.2008.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal hyperperfusion in Alzheimer's disease

Abstract: Many of the regions with the earliest atrophy in Alzheimer's Disease (AD) do not show prominent deficits on functional imaging studies of flow or metabolism. This paradox may provide unique insights into the pathophysiology of AD. We sought to examine the relationship between function and atrophy in AD using MRI blood flow and anatomic imaging. 22 subjects diagnosed with AD, mean Mini Mental State Exam (MMSE) score 22.2, and 16 healthy elderly controls were imaged with a volumetric arterial spin labeling blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
152
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(177 citation statements)
references
References 57 publications
22
152
2
1
Order By: Relevance
“…Cross-sectional studies thus have suggested that patients with very mild AD and mild cognitive impairment (MCI) may have hippocampal hyperperfusion. 32,33 This would be consistent with other work showing increased medial temporal activation during performance of memoryrelated tasks in MCI 35 and hippocampal neuronal hypertrophy in asymptomatic AD. 36 One longitudinal study related hippocampal activation to subsequent cognitive decline in AD.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…Cross-sectional studies thus have suggested that patients with very mild AD and mild cognitive impairment (MCI) may have hippocampal hyperperfusion. 32,33 This would be consistent with other work showing increased medial temporal activation during performance of memoryrelated tasks in MCI 35 and hippocampal neuronal hypertrophy in asymptomatic AD. 36 One longitudinal study related hippocampal activation to subsequent cognitive decline in AD.…”
supporting
confidence: 91%
“…18 The latter step was reported in a study that found more significant hyperperfusion in hippocampus in patients with mild AD after correction. 23 However, similar effects but with a slightly reduced significance level were obtained if the second Jacobian-based correction was not applied. Accordingly, the observed hypoperfusion likely reflects functional changes beyond those that can be attributed to atrophy alone.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Other studies have paradoxically showed that early on, cerebral blood flow is increased in the hippocampus and other regions in Alzheimer patients. 6 Various clinical, epidemiological and pathological studies suggest that AD is more frequently associated with stroke than expected; vascular brain lesions and those connected with AD are often related; β-amyloid plaques are more abundant in non-demented patients who have died from coronary artery disease than in those who have died from other causes. These findings suggest that vascular pathology and AD are directly related or at least share common determinants.…”
Section: Introductionmentioning
confidence: 99%